Evaluating The Effectiveness Of An Educational Unit Using The Whole Language Approach To Develop Arabic Creative Writing Skills For Intermediate Level/ تقييم فاعلية وحدة تعليمية بالمدخل الكلي لتنمية بعض مهارات الكتابة الإبداعية لدارسي اللغة العربية بالمستوى المتوسط - Kharashi, Nasirudeen Abdur Razaq; Mohd Noor, Siti Salwa Binti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Creative writing skill represents the most essential skill for students, and it is one of the most important means of acquiring knowledge and information, it is one of the basic skills that should be emphasized for Arabic-speaking students in general and non-native speakers in particular; therefore, this study aimed to identify and evaluate the effectiveness of a proposed educational unit in the light of the whole language approach in developing some creative writing skills required for foreign learners at the intermediate level. To achieve this goal, the researcher developed research tools that consisted of indicators of some necessary creative writing skills. A list of criteria for the content of the proposed educational unit to develop some of the necessary creative writing skills. The proposed educational unit is in the light of the holistic approach to developing some necessary creative writing skills. A pre-and post-test on the development of some necessary creative writing skills. The sample of the study consisted of thirty male and female students from the preparatory year programme at the Language Centre of the Faculty of Languages and Communication at Universiti Sultan Zainal Abidin, Kuala Terengganu Malaysia. The researcher adopted the descriptive and quasi-experimental approach in applying the study tools. After testing the study tools and analyzing the results of the pre and post-tests, the study found the effectiveness of the proposed educational unit based on the whole language approach in developing some of the creative writing skills required by the learners in the study group. The study also derived some recommendations and suggestions, the most important of which is: The need for Arabic language teachers to train students on creative writing skills using the whole language approach. The importance of reviving school activities related to writing, such as Journalism group and school radio. The importance of activating school activities related to writing, such as the journalism group and school radio, as well as allocating a course that deals with the areas of creative writing to train students in these areas, including exercises and activities that help them master these skills.